Globalising Southern approaches to reducing extreme poverty: Policy adoption of BRAC’s targeting the ultra poor graduation program - Hashemi, Syed M.; de Montesquiou, Aude (Taylor and Francis, 2024)
This article was published in The Development in Practice [©2024 Rights managed by Taylor & Francis] and the definite version is available at: https://doi.org/10.1080/09614524.2024.2317836 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2024.2317836